Probability applications in mechanical design - Fisher, Franklin E., 1933-; Fisher, Joy R., 1940- (New York : Marcel Dekker, 2000)
This text seeks to clarify mechanical fatigue and design problems by applying probability and computer analysis, and further extending the uses of probability to determine mechanical reliability and achieve optimization. It solves examples using commercially available software.
Preface; Contents; Data Reduction; Application Mechanical of Probability to Design; OptimumDesign; Reliability; Appendix A Linearization of the WeibullEquation; Appendix B Monte Carlo Calculations; Appendix C Computer Optimization Routines [3.20]; Appendix D Mechanical Failure Rates for Non-Electronic Reliability; Appendix E Statistical Tables; Appendix F Los Angeles Rainfall 1877-1997; Appendix G Software Considerations; Author Index; Subject Index.
Includes bibliographical references and indexes.
eBooks on EBSCOhost
Keywords: Machine design -- Statistical methods; Probabilities; Probability; Machines -- Conception et construction -- Méthodes statistiques; Probabilités.; probability; TECHNOLOGY & ENGINEERING -- Machinery; Machine design -- Statistical methods; Probabilities; Andre fag (naturvidenskab og teknik) -- Andre fag